2016
DOI: 10.3892/ol.2016.5153
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of metastasis of thyroid cancer cells via NRP-2-mediated induction

Abstract: Abstract. Tumor-node-metastasis is one of the leading causes of morbidity and mortality in thyroid cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Progressive dedifferentiation of DTC is accompanied by loss of the sodium iodide symporter (NIS) that is required for iodine uptake. Poorly differentiated foci with loss of iodine avidity exhibit parallel development of F‐Fludeoxyglucose (FDG)‐PET positivity so that FDG‐PET‐positive disease is more likely to be refractory . Radioiodine refractory disease is far more common in older patients: those with large tumour burden and those with poorly differentiated subtypes such as tumours with Hurthle cell histology …”
Section: Defining Radioiodine Refractory Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Progressive dedifferentiation of DTC is accompanied by loss of the sodium iodide symporter (NIS) that is required for iodine uptake. Poorly differentiated foci with loss of iodine avidity exhibit parallel development of F‐Fludeoxyglucose (FDG)‐PET positivity so that FDG‐PET‐positive disease is more likely to be refractory . Radioiodine refractory disease is far more common in older patients: those with large tumour burden and those with poorly differentiated subtypes such as tumours with Hurthle cell histology …”
Section: Defining Radioiodine Refractory Diseasementioning
confidence: 99%
“…17 VEGF is upregulated in DTC and one of its coreceptors, NRP-2, has been implicated in metastases through enhancement of invasion and motility in thyroid cancer cells. 18,19 Several studies have shown a correlation between VEGF receptor expression and metastasis in PTC. 18 Anti-angiogenic therapies have become established as treatments for advanced DTC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, stromal cells could modulate Decorin to control thyrocytes growth. Further, interactions for CYR61 (associated with Graves’ Disease (38)), LRP2 / Megalin (involved in thyroglobulin processing (39)) and NRP2 (associated with thyroid cancer metastasis (40)) were identified (Fig. 3C).…”
Section: Discussionmentioning
confidence: 98%
“…Beyond, VEGF-C-mediated invasion and migration of thyroid cancer cells required the expression of Nrp2. 16,17 Nrp2 intracellular domain interacts Roles of Nrp2/VEGF-C Axis in a Series of Recurrent Lymphangioma Yan et al 341…”
Section: Discussionmentioning
confidence: 99%